Breast imaging hindered during covid-19 pandemic, in Brazil - Jordana de Faria Bessa (Universidade de São Paulo, 2021)
ABSTRACT OBJECTIVE: To report the decrease in breast imaging after covid-19 pandemic, obtaining the number of mammograms performed in 2019 and 2020. Additionally, to investigate if there was an increase in the proportion of women undergoing mammography for diagnostic purposes, with palpable lesions. METHOD: This is a cross-sectional study, based on the number of mammograms performed by the Brazilian public health services, provided by DATASUS, an open access database. Mammograms from private institutions were not included. This study compares the number of mammograms performed in 2019 and 2020, in women aged 50-69 years, stratified by month, in each federal state, and the presence of palpable lumps (physician-reported). RESULTS: In total, 1,948,471 mammograms were performed in 2019 and 1,126,688 in 2020, for the population studied. These values represent a 42% decline. Monthly, a significant decreased is observed after April 2020. The results varied slightly according to federal state; yet the entire country was affected. Rondônia was the most affected state, with 67% decline. The proportion of women presenting palpable lumps increased from 7.06% on average in 2019 to 7.94% in 2020 (OR = 1.135, 95%CI 1.125-1.145, p = 0,001). DISCUSSION: The number of mammograms performed in 2020 declined considerably. Out of the women who presented for mammogram, the proportion of palpable lumps was significantly higher in 2020. Considering the detection rate of digital mammography, the loss of 800,000 exams means 4,000 undiagnosed breast cancer cases, by the end of 2020.